Evaluation of enzyme kinetic parameters to produce methanol using Michaelis-Menten equation - Norazwina, Zainol; Siti Natrah, Ismail (Department of Chemical Engineering, Diponegoro University, 2019)
Determination of kinetic parameters of enzymes is important in biotechnology research. It is also one of the most challenging processes in methanol production. The activity of enzyme is determined in term of initial rates at various substrate concentrations. The enzymatic hydrolysis of methanol by pectin methyl esterase (PME) enzyme was investigated at 25 °C and pH 9 over the reaction time range from 0 to 90 min. In this study, the parameters of the enzyme's kinetic, KM and Vmax were directly determined using a modified Michaelis-Menten equation by applying the Lineweaver-Burk plots. Besides, nonlinear regression of Michaelis-Menten equation was calculated based on Euler’s and Runge-Kutta 4th order methods by using Solver supplement application. The result of kinetic constant was tested by comparing the experimental data with model predictions. It was found that Euler and Runge-Kutta method was successful in determining the kinetic parameter rather than Lineweaver-Burk plot. The application of the Michaelis-Menten equation describes the enzyme kinetic very well. From the kinetic analysis, it showed the good agreement between the result obtained and the predictions model in the production of methanol using PME enzyme.